[Acute pyelonephritis in the neonatal period] [Article in Italian] • Pielonefrite acuta in epoca neonatale - Giovanni Ottonello; Angelica Dessì; Danila Manus; Anna Paola Pinna; Fabiana Sau; Vassilios Fanos (Hygeia Press di Corridori Marinella, 2014)
Urinary tract infections (UTIs) represent one of the most common pathological conditions in children. It is estimated that even in the countries with the most advanced health care programmes, such as the United States and Europe, UTIs represent the most common serious infections in pediatrics. In the earliest stages of life, UTIs represent the most common febrile illness, although the non specific clinical presentation often leads to diagnostic underestimation. Neonatal UTIs surely represent a special case among pediatric UTIs and need specific considerations and separate treatment with respect to later age: it is no coincidence that the main national and international guidelines for the diagnosis and treatment of UTIs, such as those issued by the American Academy of Pediatrics (AAP) and by the Working Group of the Italian Society of Pediatric Nephrology, exclude from their indications the newborn and the infant under two months of age. Low gestational age, low birth weight, association with malformative uropathies are considered specific risk factors. Breastfeeding has a protective effect. E. coli is the major responsible of UTI in term newborns and infants, followed by K. pneumoniae, Proteus spp., E. cloacae. Finally, Candida spp. is very important in hospitalized children. Treatment includes the combination of ampicillin plus an aminoglycoside (frequently gentamicin). The article shows the main aspects of the urinary tract infections in the neonatal period and a review of the most recent literature on the subject. Articoli Selezionati del "3° Convegno Pediatrico del Medio Campidano" · Guspini · 25 Maggio 2013 Guest Editor: Roberto Antonucci